«HE WHO STARTED EVERYTHING WITH WORD»: TARAS SHEVCHENKO IN SVIATOSLAV HORDYNSKY’S POETRY WORKS - Mocherniuk, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The manifold forms of Sviatoslav Hordynsky’s dialogue with the works of Taras Shevchenko have been traced. Much attention has been paid to the Shevchenko’s theme in literary studies and art criticism of Sviatoslav Hordynsky. The poetry works in which the author refreshes the image of Shevchenko and some of his works («Shevchenko over Caspian», «Three verses», «Kanev» and other). The poetry shevchenkiana of Sviatoslav Hordynsky is one of modes of author’s identity as a artist.